Multi slot amplitude coding technique for high speed optical fiber communication system - Talib, Rahmat (2015)
The rapid progress of the high speed optical communications system is driven by the exponential growth of users demand on information and services. The trend towards high speed and high capacity transmission system are multiplexing technique such as electrical time division multiplexing (ETDM) and duty cycle division multiplexing (DCDM). Unfortunately, ETDM bit rate is limited by the speed of electronic devices and DCDM suffers from increased spectral width when the number of tributary increased. Therefore, in this research, a new multiplexing technique is proposed, known as Multi Slot Amplitude Coding (MSAC). In this technique, three, four and five tributaries can be achieved with less number of slots compared to DCDM. The performance of 310 Gbit/s MSAC is -26 dBm for receiver sensitivity (RS) and 25.5 dB for optical signal-to-noise ratio (OSNR). The improvement of 3.5 dB for RS and 3.7 dB for OSNR are obtained when optimize level spacing is implemented. When compared to DCDM, the spectral width is reduced by around 25%, not less than 55% improvement of chromatic dispersion (CD) tolerance, 0.6 dB better RS, and 1.5 dB better OSNR. The spectral width for 310 Gbit/s, 410 Gbit/s and 510 Gbit/s MSAC is 60 GHz, which indicates improvement of spectral efficiency. Optical spectrum of MSAC has spectral line at 10 GHz to provide an accurate clock frequency at symbol rate. In addition the performance of MSAC technique is simulated under self phase modulation (SPM) effect. The result shows that the maximum launched optical power is +12.79 dBm and +12.62 dBm for 50 km and 80 km standard single mode fiber (SSMF) with 100% compensation of dispersion using dispersion compensation fiber (DCF) at receiver. Moreover, SPM threshold improves around 2.7 dB when adopting the pre and post dispersion compensation method.